Nusinersen efficacy data for 24‐month in type 2 and 3 spinal muscular atrophy. Issue 3 (15th February 2022) - Pane, Marika; Coratti, Giorgia; Pera, Maria Carmela; Sansone, Valeria A.; Messina, Sonia; d'Amico, Adele; Bruno, Claudio; Salmin, Francesca; Albamonte, Emilio; De Sanctis, Roberto; Sframeli, Maria; Di Bella, Vincenzo; et al.
Abstract: The study reports real world data in type 2 and 3 SMA patients treated for at least 2 years with nusinersen. Increase in motor function was observed after 12 months and during the second year. The magnitude of change was variable across age and functional subgroup, with the largest changes observed in young patients with higher function at baseline. When compared to natural history data, the difference between study cohort and untreated patients swas significant on both Hammersmith Functional Motor Scale and Revised Upper Limb Module both at 12 months and at 24 months.